Penerapan Metode Bernyanyi Untuk Meningkatkan Religiusitas Anak Usia Dini Di TK Al Hikmah Pasir Putih Siak Hulu - Saputra, Waldi; Ramadhan, Syahri; Sulistiani, Sulistiani (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This research purposes was to find out the increasing of the early childhood students’ religiosity through singing method at TK Al-Hikmah Pasir Putih Siak Hulu. The research was classroom action research which was conducted in two cycles and each cycle in two meetings. To ensure the research conducted well, the researcher used certain steps; 1) Action planning, 2) Action implementation, 3) Observation, and 4) Reflection. The subjects in this research were 15 the early childhood students at class B1 TK Al-Hikmah Pasir Putih Siak Hulu in 2020-2021 academic year. While the object of this research was application of the singing method to increase religiosity at TK Al-Hikmah Pasir Putih. The data collection techniques were observation and presented in percentage forms. The research results were there was an improving the early childhood students’ religiosity before and after the action was taken to cycle I and from cycle I to cycle II. Before the actions 4 or 26.67% the early childhood students were classified in undeveloped category. in the first cycle of the second meeting and in the second cycle of the second meeting, no early childhood students or 0% was classified in undeveloped category. Before the actions 5 or 33.33 % the early childhood students were classified in developed category. In the first cycle of the second meeting there were 2 early childhood students or 13.33 % were classified in developed category. in the second cycle of the second meeting, there were 0 the early childhood students or 0% was classified in developed category. Before the action there were 6 the early childhood students or 40.00% were classified in well developed category. in the first cycle of the second meeting there were 5 the early childhood students or 33.33%, and in the second cycle of the second meeting, there were 3 the early childhood students or 20% were classified in well developed category. in the first cycle of the second meeting there was an increase of the early childhood students’ religiosity at 53.33%, the second cycle of the second meeting there was an increase in 80 %. It proved that singing method improved the early childhood students’ religiosity at TK Al-Hikmah Pasir Putih Siak Hulu.